1983
DOI: 10.1289/ehp.834765
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of vehicle emissions for chemical analysis and biological testing.

Abstract: Representative dilution tube sampling techniques for particulate and gas phase vehicle emissions are described using Teflon filter media and XAD-2 resin. More than 90% of the total gas (C8-C18) and particulate direct acting Ames assay mutagenicity (TA 98) was found in the particulate phase. The gas and particulate phase material was fractionated by HPLC into nonpolar, moderately polar and highly polar chemical fractions. The moderately polar chemical fraction of the particulates contained more than 50% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
140
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(146 citation statements)
references
References 47 publications
4
140
0
2
Order By: Relevance
“…Interestingly, the quantum yields of these hydroxynitropyrenes are similar in the alcohols, while in acetonitrile the yield of the 1-OH-2-NO 2 Py isomer is much higher (10 to 45 times in N 2 saturated solutions and 4 to 17 times in O 2 saturated solutions). Because 1-OH-2-NO 2 Py is found in ambient air but not in diesel particles 23 , while the other isomers have been detected only in diesel particles 12 , our results suggest that the photochemical formation of the 1-OH-2-NO 2 Py in air particles will be favorably formed under conditions in which 1-NO 2 Py is encountered in a polar aprotic environment under low humidity conditions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Interestingly, the quantum yields of these hydroxynitropyrenes are similar in the alcohols, while in acetonitrile the yield of the 1-OH-2-NO 2 Py isomer is much higher (10 to 45 times in N 2 saturated solutions and 4 to 17 times in O 2 saturated solutions). Because 1-OH-2-NO 2 Py is found in ambient air but not in diesel particles 23 , while the other isomers have been detected only in diesel particles 12 , our results suggest that the photochemical formation of the 1-OH-2-NO 2 Py in air particles will be favorably formed under conditions in which 1-NO 2 Py is encountered in a polar aprotic environment under low humidity conditions.…”
Section: Discussionmentioning
confidence: 68%
“…811 In fact, more than 90% of the mutagenicity for the total exhaust emitted from a diesel engine was found in the particulate phase, and can be associated to nitro-PAHs. 1213 …”
Section: Introductionmentioning
confidence: 99%
“…There are numerous cites on the larger molecular weight PAHs for quinone formation, and therefore a particular PAH may lead to DTT activity that reflects a number of quinone isomers formed from the parent compound. Schuetzle et al [34] reported a wide range of organic compounds generated by vehicles, including PAH-quinones, PAH ketones, and carboxaldehydes, all of which may be transformed to quinones via atmospheric chemistry or biotransformation. Other compounds that have potential DTT activity include aromatic nitro-PAH groups that are formed via atmospheric chemistry [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds that have potential DTT activity include aromatic nitro-PAH groups that are formed via atmospheric chemistry [35]. Schuetzle et al [34] reported a number of nitro-PAHs from vehicle emissions. The emissions of nitro-PAHs from diesel vehicles have been described in a wide range of publications summarized by Arey [35].…”
Section: Discussionmentioning
confidence: 99%
“…Diesel exhaust particles (DEPs) are carbon-based particles containing various organic compounds, including polycyclic aromatic hydrocarbons and nitroaromatic compounds adsorbed onto the carbonaceous core (Schuetzle, 1983; Schuetzle et al, 1981). Diesel exhaust is a complex and variable mixture of gases, vapors, and particulates containing numerous chemicals.…”
Section: Introductionmentioning
confidence: 99%